A multisubstrate reductase from Plantago major: structure-function in the short chain reductase superfamily. Issue 1 (December 2018) - Fellows, Rachel; Russo, Christopher; Silva, Catarina; Lee, Soon; Jez, Joseph; Chisholm, John; Zubieta, Chloe; Nanao, Max H.
Abstract The short chain dehydrogenase/reductase superfamily (SDR) is a large family of NAD(P)H-dependent enzymes found in all kingdoms of life. SDRs are particularly well-represented in plants, playing diverse roles in both primary and secondary metabolism. In addition, some plant SDRs are also able to catalyse a reductive cyclisation reaction critical for the biosynthesis of the iridoid backbone that contains a fused 5 and 6-membered ring scaffold. Mining the EST database ofPlantago major, a medicinal plant that makes iridoids, we identified a putative 5β-progesterone reductase gene, PmMOR (P .major multisubstrate oxido-reductase ), that is 60% identical to the iridoid synthase gene fromCatharanthus roseus . The PmMOR protein was recombinantly expressed and its enzymatic activity assayed against three putative substrates, 8-oxogeranial, citral and progesterone. The enzyme demonstrated promiscuous enzymatic activity and was able to not only reduce progesterone and citral, but also to catalyse the reductive cyclisation of 8-oxogeranial. The crystal structures of PmMOR wild type and PmMOR mutants in complex with NADP+ or NAD+ and either 8-oxogeranial, citral or progesterone help to reveal the substrate specificity determinants and catalytic machinery of the protein. Site-directed mutagenesis studies were performed and provide a foundation for understanding the promiscuous activity of the enzyme.